A New CuSe-TiO2-GO Ternary Nanocomposite: Realizing a High Capacitance and Voltage for an Advanced Hybrid Supercapacitor - Muhammad Sajjad; Abdul Jabbar Khan; Sayed M. Eldin; Asma A. Alothman; Mohamed Ouladsmane; Patrizia Bocchetta; Waqas Ul Arifeen; Muhammad Sufyan Javed; Zhiyu Mao (Nanomaterials, 2022)
A high capacitance and widened voltage frames for an aqueous supercapacitor system are challenging to realize simultaneously in an aqueous medium. The severe water splitting seriously restricts the narrow voltage of the aqueous electrolyte beyond 2 V. To overcome this limitation, herein, we proposed the facile wet-chemical synthesis of a new CuSe-TiO2-GO ternary nanocomposite for hybrid supercapacitors, thus boosting the specific energy up to some maximum extent. The capacitive charge storage mechanism of the CuSe-TiO2-GO ternary nanocomposite electrode was tested in an aqueous solution with 3 M KOH as the electrolyte in a three-cell mode assembly. The voltammogram analysis manifests good reversibility and a remarkable capacitive response at various currents and sweep rates, with a durable rate capability. At the same time, the discharge/charge platforms realize the most significant capacitance and a capacity of 920 F/g (153 mAh/g), supported by the impedance analysis with minimal resistances, ensuring the supply of electrolyte ion diffusion to the active host electrode interface. The built 2 V CuSe-TiO2-GO||AC-GO||KOH hybrid supercapacitor accomplished a significant capacitance of 175 F/g, high specific energy of 36 Wh/kg, superior specific power of 4781 W/kg, and extraordinary stability of 91.3% retention relative to the stable cycling performance. These merits pave a new way to build other ternary nanocomposites to achieve superior performance for energy storage devices.